The Relationship between Weight Gain of Pregnant Women and Interpretation of Fetal Weight at the Gynecology Polyclinic of RSIA Muhammadiyah Probolinggo - Nuri As-saadatul Ulya; Mega Silvian Natalia; Tutik Ekasari (NHM PRESS, 2023)
In pregnant women, weight gain is influenced by the nutritional status and diet of the mother, namely the pattern of staple foods and animal side dishes. In addition to weight gain of pregnant women, there are other things that must be considered, namely fetal weight gain, because fetal weight gain is one of the things related to fetal growth. One of the ways to detect fetal growth is by measuring the Fetal Weight Interpretation (TBJ). TBJ is one way to estimate fetal weight while still in the uterus, it is useful for monitoring fetal growth, so that it can detect early the possibility of abnormal fetal growth. Abnormal fetal growth tends to experience problems both during labor and postnatally, including IUGR, macrosomia, and low birth weight. The purpose of this study was to determine the relationship between maternal weight gain and the interpretation of fetal weight. The research design used in this study was correlation analytic with a cross sectional design. In this study, researchers examined the risk factor is weight gain of pregnant women and The effect factor is the result of calculation of the interpretation of fetal weight. The sample of this study were all 36-38 weeks pregnant women in the gynecology polyclinic of RSIA Muhammadiyah Probolinggo city in June – July 2022 which matched the inclusion and exclusion criteria of 35 pregnant women. Birth cases at RSIA Muhammadiyah Probolinggo saw an increase in cases of LBW births, namely in 2020 by 98 babies to 119 LBW babies in 2021. Of the 35 respondents studied, most of the respondents (77.2%) experienced weight gain of between 11.3 up to 15.8 kg. The body mass index (BMI) of the mother before pregnancy at most (91.4%) had a BMI of 18.5-25 in the normal category. the results of the calculation of the interpretation of fetal weight using the modified niswander formula most (85.7%) weigh between 2,400 to 3,100 grams. While pregnant women with weight gain between 11.3 - 15.8 kg, most (77.1%) have an interpretation of fetal weight between 2,400 - 3,100 grams. The results of the Spearman Rank Analysis Test obtained the value of value < , where the value of value is 0.004 and the value of 0.05 (0.004 <0.05) and the direction of the correlation is seen in the correlation coefficient number is positive, namely 0.472 so it can be concluded that there is a relationship between the weight gain of pregnant women and the interpretation of fetal weight calculated using the modified niswander formula.